ANTIMICROBIAL STEWARDSHIP WARDROUNDS—ARE WE MAKING A DIFFERENCE?. Issue 8 (11th July 2014) - Kirk, E; Wade, P
Abstract : Aims: To evaluate the interventions made by the Antimicrobial Stewardship (AMS) multidisciplinary team at a tertiary paediatric hospital and determine their significance. Methods: Data on the first 30 referrals to the AMS ward round were recorded. Data included detailed information on the patient case and the particular interventions made. This information was then assessed by three consultants (1 Infectious Diseases pharmacist and 2 paediatric Infectious Diseases physicians) and the intervention(s) made to each patient were classified into low, moderate or high significance. Significance was debated until a unanimous decision was reached. The data were analysed using Excel. Results: Data was collected over a three month period with 57 interventions made on the 30 patients. The interventions were classified into 12 categories covering areas such as choice of drug, dose, route and duration of therapy. Interventions that were made most frequently were: drug stopped (33%, n=19), duration specified (19%, n=11) and drug started (9%, n=5). The majority of cases (60%) were classified as having interventions of moderate significance, with 23% classified as low significance and 17% (5 cases) classed as being of high significance. A pharmacist was significantly involved in, or initiated the intervention in 80% of the cases. Conclusion: This pilot introduction of an AMS round within a tertiary paediatric hospital has demonstrated the benefits that can be achieved. Of the interventions made, more than 75% were of moderate to high significance, resulting in optimisation of patient therapy, reduced antimicrobial usage, facilitation of patient discharge and economic savings to the Trust. Other expected benefits would include reduction of or prevention of emergence of resistance, one of the key mandates of an AMS team. The results also show the importance of the pharmacist as part of the multidisciplinary team. Further work is required to embed the AMS program into routine practice, to develop prioritisation rules to better focus resources, and to consider more frequent ward rounds to enable input to the care of more patients.